2010
DOI: 10.1080/1067828x.2010.511986
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Support for Multidimensional Treatment Foster Care in Reducing Substance Use in Delinquent Boys

Abstract: Although effective outpatient treatments have been identified for the well-documented negative outcomes associated with delinquency and substance use, effective treatments for youths in out-of-home care are rare. In this study, 12- and 18-month substance use outcomes were examined for a sample of 79 boys who were randomly assigned to Multidimensional Treatment Foster Care (experimental condition) or to group care (comparison condition). The boys in the experimental condition had lower levels of self-reported d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Similar to the alcohol outcomes, all of the interventions helped engender a reduction in marijuana use -however, just three of the interventions had a statistically significant effect on marijuana reduction (Braukmann et al, 1985;Henggeler et al, 1999;Smith, Chamberlain, & Eddy, 2010). As shown in Table 4, Braukmann et al (1985) found significantly greater reduction in marijuana use frequency among adolescent offenders who participated in Teaching Families compared to adolescent offenders who did not (Hedges's g = −1.991; 95% Confidence Interval = − 2.344 to − 1.638; p b .001).…”
Section: Marijuana Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar to the alcohol outcomes, all of the interventions helped engender a reduction in marijuana use -however, just three of the interventions had a statistically significant effect on marijuana reduction (Braukmann et al, 1985;Henggeler et al, 1999;Smith, Chamberlain, & Eddy, 2010). As shown in Table 4, Braukmann et al (1985) found significantly greater reduction in marijuana use frequency among adolescent offenders who participated in Teaching Families compared to adolescent offenders who did not (Hedges's g = −1.991; 95% Confidence Interval = − 2.344 to − 1.638; p b .001).…”
Section: Marijuana Outcomesmentioning
confidence: 89%
“…As shown in Table 4, Braukmann et al (1985) found significantly greater reduction in marijuana use frequency among adolescent offenders who participated in Teaching Families compared to adolescent offenders who did not (Hedges's g = −1.991; 95% Confidence Interval = − 2.344 to − 1.638; p b .001). Henggeler et al (1999) found multisystemic therapy to successfully decrease marijuana use compared to a treatment as usual control group at the 130 day follow-up (Hedges's g = − 0.390; 95% Confidence Interval = − 0.758 to − 0.022; p = .038), and Smith et al (2010) found multidimensional treatment foster homes to be effective compared to group care at the 18 month follow-up (Hedges's g = −0.64; 95% Confidence Interval = −1.13 to -.016; p = .02).…”
Section: Marijuana Outcomesmentioning
confidence: 97%
“…Consequently, foster youth tend to exhibit higher rates of smoking compared to youths in the general population, with 30%–60% reporting lifetime smoking, and 10%–40% reporting current smoking (Braciszewski & Colby, 2015; Coleman-Cowger, Green, & Clark, 2011; Fettes & Aarons, 2011; Scott, Munson, McMillen, & Ollie, 2006; Siegel et al, 2016; Snyder & Medeiros, 2013). The rates of smoking may be even higher among certain vulnerable subgroups within the foster care population, such as youths who have experienced homelessness, residential placements, or criminal justice involvement (Hudson & Nandy, 2012; Smith, Chamberlain, & Eddy, 2010; Strack, Anderson, Graham, & Tomoyasu, 2007). Adolescents who “age-out” of foster care without a permanent living arrangement may also be more vulnerable for engagement in risky behaviors, including substance use (Braciszewski & Colby, 2015; Kohlenberg, 2002; Pilowsky & Wu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous positive outcomes have been observed in the program as it has been employed with troubled adolescents. In comparison to adolescents in a regular group care, those receiving the MTFC intervention spent fewer days incarcerated (Fisher & Chamberlain, 2000), engaged in fewer delinquent behaviors (Fisher & Chamberlain, 2000), committed fewer violent offenses (Eddy, Whaley, & Chamberlain, 2004), had lower rates of substance use (Smith, Chamberlain, & Eddy, 2010), and had fewer associations with deviant peers (Leve, Chamberlain, & Reid, 2005). Additionally, changes in family management practices and associations with deviant peers, critical targets of the MTFC intervention, appear to mediate improvements in delinquent behaviors (Eddy & Chamberlain, 2000; Leve & Chamberlain, 2005).…”
Section: Development Of the Mtfc Intensive Intervention For High-riskmentioning
confidence: 99%